2020
DOI: 10.24815/siele.v7i1.15586
|View full text |Cite
|
Sign up to set email alerts
|

How do foreign language teachers motivate students in language learning?

Abstract: Motivation is one of the keys to success in the language learning process. It is a crucial factor for students in learning a foreign language, and the teachers’ ways to motivate students are also essential. This study aims to investigate language teachers’ ways in motivating students in learning foreign languages. The participants in this study are eight foreign language teachers including English, Arabic, and French teachers. Data were collected through open-ended questionnaires with the teachers. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…As the results showed that there are more students who got moderate level of anxiety and low level of anxiety, with only one student with a high level of anxiety, therefore the teacher urgently needs to help these students to reduce their anxiety. Some strategies to use are such as enhancing students' self-confidence (Sari et al, 2020), motivating students to speak in English and not to be worried about making mistakes (Rahman & Sahayu, 2020), involving students in English programs and asking students to overcome their anxiety by being well prepared for class, having an active role in class and always practicing with peers (Hanifa, 2018). Riasati (2011) further informed that teachers can overcome students' anxiety by removing the fear of tests, establishing friendly relationships with students, running pair and work activities, increasing students' motivation to learn the language, and enhancing students' self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…As the results showed that there are more students who got moderate level of anxiety and low level of anxiety, with only one student with a high level of anxiety, therefore the teacher urgently needs to help these students to reduce their anxiety. Some strategies to use are such as enhancing students' self-confidence (Sari et al, 2020), motivating students to speak in English and not to be worried about making mistakes (Rahman & Sahayu, 2020), involving students in English programs and asking students to overcome their anxiety by being well prepared for class, having an active role in class and always practicing with peers (Hanifa, 2018). Riasati (2011) further informed that teachers can overcome students' anxiety by removing the fear of tests, establishing friendly relationships with students, running pair and work activities, increasing students' motivation to learn the language, and enhancing students' self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…'Integrativeness' specifically conceptualises language learners' desire to acquire another language to communicate with others in the native language community (Azar & Tanggaraju, 2020). However, for language learners today, the English language represents not only the native English community but also the English language users all over the world, including Asians and Africans (Lai, 2013;Rahman & Sahayu, 2020;Sa'adah et al, 2018;Sung, 2013). Hence, this leads to the re-conception of the fundamental theories related to motivational literature in the area of Second Language Acquisition (SLA).…”
Section: Introductionmentioning
confidence: 99%
“…Being strict and motivated to follow the time allotment to finish the task correlates with the findings where motivation is helpful on reading comprehension activities (Ahmadi, 2016). It is also supported by the finding where even non-verbal motivation is also seen as a prominent aspect (Rahman et al, 2020).…”
Section: Discussionmentioning
confidence: 66%